2017
DOI: 10.1074/jbc.m117.792549
|View full text |Cite
|
Sign up to set email alerts
|

Structural analysis of the dual-function thioesterase SAV606 unravels the mechanism of Michael addition of glycine to an α,β-unsaturated thioester

Abstract: Thioesterases catalyze hydrolysis of acyl thioesters to release carboxylic acid or macrocyclization to produce the corresponding macrocycle in the biosynthesis of fatty acids, polyketides, or nonribosomal peptides. Recently, we reported that the thioesterase CmiS1 from sp. MJ635-86F5 catalyzes the Michael addition of glycine to an α,β-unsaturated fatty acyl thioester followed by thioester hydrolysis in the biosynthesis of the macrolactamantibiotic cremimycin. However, the molecular mechanisms of CmiS1-catalyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…However the recent biochemical and structural characterization of three ScoD homologues indicated that these thioesterases have dual functions with enzymatic hydrolysis occurring immediately after the Michael addition, both steps mediated by a single Gly residue in the active site. 1012 These results raised the question of what the true substrate of ScoE is. We thus initiated an effort to reconstitute the in vitro activity of ScoE using various substrates that were chemically or chemoenzymatically synthesized.…”
mentioning
confidence: 99%
“…However the recent biochemical and structural characterization of three ScoD homologues indicated that these thioesterases have dual functions with enzymatic hydrolysis occurring immediately after the Michael addition, both steps mediated by a single Gly residue in the active site. 1012 These results raised the question of what the true substrate of ScoE is. We thus initiated an effort to reconstitute the in vitro activity of ScoE using various substrates that were chemically or chemoenzymatically synthesized.…”
mentioning
confidence: 99%
“…[ 79‐80 ] Moreover, SAV606, a homolog to Rv0098, identified from S. avermitilis MA‐4680, has a dual function. [ 81 ] In addition to triggering the hydrolysis of the corresponding thioester to form N ‐carboxymethyl‐3‐aminononanoate ( 3 ), it also catalyzes the addition of glycine onto 24 (Figure 10B). Rv0099 , also known as FadD10, a ScoC homolog, likely serves a function of as fatty acyl‐AMP ligase.…”
Section: Isonitrile Formation Through Decarboxylation‐assisted Desatumentioning
confidence: 99%
“…The proposed pathway thus accounts for the necessity and sufficiency of these five core biosynthetic enzymes for INLP synthesis (Figure ). However the recent biochemical and structural characterization of three ScoD homologues indicated that these thioesterases have dual functions with enzymatic hydrolysis occurring immediately after the Michael addition, both steps mediated by a single Gly residue in the active site . These results raised the question of what the true substrate of ScoE is.…”
Section: Figurementioning
confidence: 99%